Delay in Criminal Justice System in India - The Way Forward - Pradeep Kumar Saxena; Dr. Vinod Kumar Saroj (International journal of economic perspectives, 2022)
It is crucial to first comprehend the nature of crime and, more crucially, penal laws because criminal law is dependent on penal laws, in order to comprehend the delay in the criminal justice system. The primary query is that why are criminal laws created. Personal security, freedom, and property security are of the utmost importance to every person. In any civilization, peace and order must be upheld if people are to live in peace without fear for their lives, limbs, or property. Only in states with efficient penal laws that are robust enough to deal with lawbreakers is this feasible. Any state must have an effective system of penal laws in order to fulfil its principal duty of maintaining law and order in the country, regardless of its philosophy or form of government, in order to be recognised as a state. The country’s penal code is unquestionably the government’s primary tool for enforcing this important task.